(untitled) (Journal of the Spanish Institute for Strategic Studies, 2023)
The strategic context and the new challenges and threats set up a new operating environment to which Armed Forces, and Air Forces, in particular, will need to adapt to if they want to maintain its operational ability and effectiveness. Warlike events and conflicts in the last two decades have demonstrated that advances in technology have radically altered the battlespace and, as a consequence, have affected the application of military power. The traditional way in which military operations are planned and executed is clearly affected. In present and future operational scenarios, more agility and flexibility as well as a high level of adaptability in the way to operate will be needed in order to maintain the strategic advantage which permit us to execute succesful military [air and space] Operations. Keywords: Operating environment, hybrid strategy, multi-domain, battlespace. operational agility.